Characterization of damage in Portuguese lupus patients: analysis of a national lupus registry. (March 2015) - Gonçalves, M J; Sousa, S; Inês, L S; Duarte, C; Borges, J; Silva, C; Romão, V C; Terroso, G; Bernardes, M; Cerqueira, M; Raposo, A; Sequeira, G; et al.
Background: Although the survival rate has considerably improved, many patients with systemic lupus erythematosus (SLE) develop irreversible organ damage.Objectives: The objectives of this paper are to characterize cumulative damage in SLE patients and identify variables associated with its presence and severity.Methods: A cross-sectional analysis of SLE patients from the Portuguese Lupus register Reuma.pt/SLE in whom damage assessment using the SLICC/ACR-Disability Index (SDI) was available was performed. Predictor factors for damage, defined as SDI ≥ 1, were determined by logistic regression analyses. A sub-analysis of patients with severe damage (SDI ≥ 3) was also performed.Results: In total, 976 patients were included. SDI was ≥1 in 365 patients, of whom 89 had severe damage. Musculoskeletal (24.4%), neuropsychiatric (24.1%) and ocular (17.2%) domains were the most commonly affected. Older age, longer disease duration, renal involvement, presence of antiphospholipid antibodies and current therapy with steroids were independently associated with SDI ≥ 1. The subpopulation with severe damage had, in addition, a greater interval between the first manifestation attributable to SLE and the clinical diagnosis as well as and more frequently early retirement due to SLE.Conclusions: This large lupus cohort confirmed that demographic and clinical characteristics as well as medication are independently associated with damage. Additionally, premature retirement occurs more often in patients with SDI ≥ 3. Diagnosis delay might contribute to damage accrual.